Implementing disability policy in teaching and learning contexts – shop floor constructivism or street level bureaucracy?. Issue 4 (19th May 2019) - Wray, Mike; Houghton, Ann-Marie
ABSTRACT: Since 1995 the UK higher education sector has been required to implement national disability related legislation. This paper reports on a study which explored the role that policies play in influencing how staff support disabled students. In particular the extent to which staff in HE behave in similar ways to those described as street level bureaucrats by (Lipsky, M. 1980. Street-Level Bureaucracy: Dilemmas of the Individual in Public Services . New York: Russell Sage Foundation). Semi-structured interviews undertaken with 34 staff in the case study university provided the substantive data. Although there was little evidence to show that policy had a direct influence on practice, it was clear that staff made considerable efforts to support disabled learners and these efforts were based on values associated with providing an equitable experience for all students. Additionally, staff were able to exercise discretion in the way they responded to disabled students and constructed responses to policies without significant influence from institutional managers, national legislation or broader policy discourse.